Recurrent urethral stricture with dual lumen managed by a single stage dorsal Onlay buccal mucosal graft Urethroplasty: a case report. Issue 8 (23rd August 2022) - Alkhayal, Abdullah; Alrabeeah, Khalid; Alsaikhan, Bader H; Alathel, Abdulaziz; Barayan, Fahad R; Alsaghyir, Abdullah
Abstract: Urethral stricture is defined as any abnormal narrowing throughout the entire length of the male urethra. Anterior urethral stricture is the most common site which accounts for more than 90% of cases in developed countries. One of the possible long-term outcomes of urethral stricture treatment is stricture recurrence. Refractory urethral strictures to initial management present surgical challenges to the reconstructive surgeon. It has been reported in the literature that buccal mucosal grafts in complex anterior urethral strictures have lately become a well-established management modality for bulbar and penile urethral strictures. Here, we are presenting an interesting case of a patient with a dual lumen urethra due to recurrent urethral stricture.